Inhibition of Polypeptide Chain Initiation in Escherichia coli by Elongation Factor G - Lee-Huang, Sylvia (1974)
We have previously reported the isolation from E. coli of a specific inhibitor of polypeptide chain initiation that is rendered ineffective when active aminoacylation of transfer RNA is taking place; this is normally the case during natural messenger RNA translation. Surprisingly, the inhibitory activity appears to be a hitherto unrecognized property of the chain elongation factor G. The following hold for preparations purified for either translocase or inhibitor activity: (1) equal electrophoretic mobility on polyacrylamide gels; (2) equal specific activities for (a) inhibition of initiation, (b) translocation, and (c) ribosome-dependent, uncoupled GTPase; and (3) similar heat sensitivity of translocase and inhibitor activities in a temperature-sensitive E. coli mutant with an altered elongation factor G. Different sites are apparently involved in translocation and inhibition because the former, but not the latter, is sensitive to p-chloromercuribenzoate and fusidic acid.